THU0624 Sleep Quality in Patients with Severe Knee Osteroarthritis. (15th July 2016) - Nuñez, M.; Nuñez, E.; Lozano, L.; Segur, J.M.; Montañana, J.; Segura, V.; Salo, S.; Alemany, X.; Sastre, S.
Abstract : Background: Sleep disturbance is closely related to chronic musculoskeletal diseases. Reports suggest 55% of patients aged >55 years sleep <6 hours (15%) with deficient or poor quality sleep (29%), insomnia (56%) and diagnosed sleep disorders (18%). Osteoarthritis (OA) is one of the most prevalent of these diseases. Older adults with OA have poorer health, worse sleep quality, more limitations in activities of daily living and more pain compared with persons without OA. The prevalence of night joint pain and sleep problems increase with the severity of OA, which negatively impacts the quality of life. Objectives: To determine whether sleep quality is associated with the health status in patients with severe knee OA. Methods: Cross-sectional observational study. Consecutive patients with severe knee OA on a waiting list for arthroplasty were included. Sociodemographic and clinical variables were determined. Patients were asked the number of hours they usually sleep and about sleep quality (whether sleep was restorative) in the previous ≥6 months, using the question: How do you usually sleep? (by Likert scale: 1=good, 2=fair, 3=poor and 4=with medication). The health status was assessed using specific and generic health-related quality of life questionnaires (HRQOL) (WOMAC and SF-36, respectively). Data analysis: Multiple linear regression models were used to analyse the association between health and sleep quality (dichotomized as 1: reparative sleep (RS)=1 and non-reparative sleep (NRS)=2, 3, 4). Dependent variables were: total WOMAC scores (TW), SF-36 physical component (PC) and mental component (MC). Independent variables were: sleep quality, age, gender, BMI, severity OA number of comorbidities and depression/anxiety. Results: 142 patients, (84% female, mean age 68.5 (SD 8.6), mean BMI 33.9 (SD 4.1), mean comorbidities 5.1 (SD 3.6) were included. The most-frequent comorbidities were hypertension 63.8%, back pain 47.5%, depression/anxiety 38.6%. Patients with RS (27%) slept a mean of 7.6 (SD 1) hours vs 6.6 (SD 1.4) hours in those with NRS (p<0.001). There was no association with the MC. Mean TW scores were 49.8 (SD 16.1) for patients with RS vs. 59.3 (SD 16.4) for patients with NRS (p=0.003). Mean PC scores were 36.1 (SD 9.5) for RS and 31.8 (SD 8.4) for NRS (p=0.009). Mean MC scores were 46.2 (SD 13.1) and 43.8 (SD 13.6) (p=0.343) for RS vs. NRS, respectively. Separate regression models showed RS was associated with better TW scores (p=0.002), with other variables not being significant, and that RS was associated with better PC scores (p=0.012) and female sex, the number of comorbidities and anxiety/depression were associated with worse PC scores (p=0.013 and p=0.004, respectively). Conclusions: Reparative sleep is associated with a better health status in OA patients on a waiting list for TKA. References: Parmelee PA et al. Sleep disturbance in osteoarthritis: linkages with pain, disability and depressive symptoms. Arthritis Care Res 2015;67(3):358 Acknowledgement: This work has been funded by the project PI/13/00948, integrated in the Plan Nacional I+D+I and co-funded by ISCIII-Subdirecciόn General de Evaluaciόn and European Regional Development Fund (ERDF). Disclosure of Interest: None declared